Um espaço, várias praças: conflitos e disputas em torno da Praça da Estação - Elena Lucia Rivero (2015)
This work analyzes a square (Praça da Estação) in Belo Horizonte in the view of the production of space from 1980 to the present. The 1980s became the starting point because heritage issue has acquired centrality in the ways of conceiving space in this decade. The 1990s revealed the existence of several squares in tension at the same place. The square in its daily live will be contrasted, on the one hand, with the square of the past, that doesnt exists anymore, and, on the other, with the square of the future as a new spatiality that will be achieved through the revitalization projects. These projects were implemented from the year 2000 and in 2010 there was a regulation of the uses of the square. We understand that these ways of conceiving the space have not excluded conflict and tension; in this sense, we recover the disputes that have been established around the interventions. We consider space as a product of social relations, so the sources of the research should reflect this diversity. Thus, we analyze documents produced by the government, the press and civil society. Finally, through field research, we think about the different ways of occupation and appropriation of the square as a public space in its daily live, in event days and as a space of manifestation.